A study of bereavement care after a sudden and unexpected death. Issue 6 (June 1996) - Dent, A; Condon, L; Blair, P; Fleming, P
Abstract : Bereaved parents' perceptions of care after the sudden, unexpected death of their child (from 1 week to 12 years), and the care that was or could be offered by statutory and voluntary agencies, was assessed in 11 health districts in seven regions of England and Wales. In these 11 districts, 185 families were identified who met the criteria of the study. Permission to contact these families was given by only 72 general practitioners. Of these, 42 families responded (58%). Sudden infant death syndrome accounted for 43% of the deaths. The results from postal questionnaires sent to both parents showed that hospital care was perceived as good on the whole, although parents would like more choices. Most parents felt that community care was inadequate, leaving many feeling isolated. In contrast, questionnaires from health visitors and general practitioners in the same health districts showed that they believed that they were the most appropriate professionals to give follow up care, but as there were few policies to guide them and little training provided, felt unable to offer support.